Transformation of the sacred and the profane in space and time case study Chinese ritual in Chinese temple in Bekasi, West Java, Indonesia - Dewi Hartati, Celerina; Rudyansjah, Tony (Kasetsart Journal of Social Sciences, 2021)
Existing discussions on the sacred and the profane have continually treated space and time in a co-extensive or unified analysis, despite the fact that in several cultures, separation between the two concepts of space and time is highly necessary in order to comprehend shifts or exchanges between the sacred and the profane. This article intends to showcase a transformation within the conception of the sacred and the profane observed in the dimension of time separate from the dimension of space, in which the dimension of time ultimately determines the conception of the sacred. In several cultures, separation between space and time is highly necessary in comprehending the conception of the sacred and shifts or exchanges between the concept of the sacred and the profane itself. For example, Chinese culture has since the beginning, separated the dimension of space and time in the conception of the sacred. This research was conducted in a Chinese temple in Bekasi, West Java, Indonesia. Through the ceremony held in the temple, the transformation of the sacred and profane in space and time can be seen.